Analysis of Employee Engagement and Relational Capital on Employee Performance at PT. Eka Tama Makmur Surabaya - Nabilla Aziza Fajar Alfiyanto; Gendut Sukarno (Indonesian Journal of Business Analytics, 2023)
Human resource management has an important role in managing, organizing, administering and establishing staffing programs that can cover employee performance issues, so that they can function productively, effectively and efficiently. This study aims to determine the effect of employee engagement and relational capital on employee performance at PT. Eka Tama Makmur Surabaya. The population in this study were all members of PT. Eka Tama Makmur Surabaya's marketing employees as many as 40 employees. The sampling technique uses a saturated sampling technique through a non-probability sampling method so that the number of samples taken is 40 employees. Smart partial least squares (PLS) is the analysis method employed. (1) Employee engagement at PT. Eka Tama Makmur Surabaya demonstrates a relationship with staff productivity; the greater the amount of involvement, the greater the firm's performance or value produced by employees. (2) Relational capital demonstrates a link between it and employee performance, and at PT. Eka Tama Makmur Surabaya, an adequate relational capital model can enhance employee performance.